2004
DOI: 10.1111/j.1469-7610.2004.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Disagreement between parent and adolescent reports of functional impairment

Abstract: Implications for diagnosis, treatment planning and outcomes measurement are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 44 publications
6
68
3
1
Order By: Relevance
“…Not only is the perceived value of an intervention or service dependent on who is asked, but some biases in the overall literature imply that certain information about interventions and services is valued more than others. Regarding the former, our satisfaction data, for example, noted that adults (parents and teachers) often rated interventions better than CYP, a finding that has been observed elsewhere, 206 and in both our satisfaction and qualitative data, there was evidence that CYP did not agree among themselves about the value of a particular intervention or which specific components were the most valuable to them.…”
Section: Different Perspectivessupporting
confidence: 76%
“…Not only is the perceived value of an intervention or service dependent on who is asked, but some biases in the overall literature imply that certain information about interventions and services is valued more than others. Regarding the former, our satisfaction data, for example, noted that adults (parents and teachers) often rated interventions better than CYP, a finding that has been observed elsewhere, 206 and in both our satisfaction and qualitative data, there was evidence that CYP did not agree among themselves about the value of a particular intervention or which specific components were the most valuable to them.…”
Section: Different Perspectivessupporting
confidence: 76%
“…The ramifications of this study also indicate that the self-reported need and severity level of emotional distress of URM should be taken seriously in the decision-making process for treatment or intervention. Disagreement between informants should not be ignored, but addressed as it can be crucial information to treatment (i.e., maladaptive avoidance behavior; relationship discord) (Kramer et al, 2004;Ferdinand et al, 2004).…”
Section: Methodological Challengesmentioning
confidence: 99%
“…The help-seeking of children and adolescents occurs frequently in the social network in which they live and is usually not initiated by them (Srebink et al, 1996), but by their parents/caretakers. Many studies have found that parents play a crucial role (more important than the adolescent self) in adolescents MHC utilization (e.g., Kramer et al, 2004, Yeh & Weisz, 2001. There is often a discrepancy between the need that adolescents report and the need that parents/ teachers report concerning MHC (Leaf et al, 1996).…”
mentioning
confidence: 99%
“…Two concepts are used regarding the potential consequences or the impact of the child's psychological symptoms: a) functional impairment, which refers to the consequences for the child's performance of everyday life functions (Üstun & Chatterji, 1997); and b) family burden, which refers to the consequences for family members (Angold et al, 1998). These concepts are especially relevant for treatment access and planning and for the monitoring of outcomes (Kramer et al, 2004). Angold, Costello, Farmer, Burns, and Erkanli (1999) and Angold et al (1998) reported, on the one hand, that children with functional impairment associated with psychological symptoms were in need of services and should be considered as suffering from a psychiatric disorder, and on the other, that perceived parental burden is a strong predictor of use of mental health services.…”
Section: Introductionmentioning
confidence: 99%